Article 6.8 - COP29 Negotiation Updates - Villarino, Eliza (2024)
The work programme for non-market approaches (NMAs) under the Paris Agreement aims to facilitate voluntary cooperation among parties to implement their NDCs in the context of sustainable development and poverty eradication. The initial focus areas include adaptation, resilience, and sustainability; mitigation measures to address climate change and contribute to sustainable development; and the development of clean energy sources. CGIAR made two submissions to the NMA track.